An evaluation of SFAS No. 130 comprehensive income disclosures - Chambers, Dennis; Linsmeier, Thomas J.; Shakespeare, Catherine; Sougiannis, Theodore (Review of accounting studies, 2007)
In this study, we provide evidence on the pricing of other comprehensive income (OCI) that differs from most evidence in prior research. Prior archival research has largely concluded that OCI is not priced by investors. In contrast, we provide evidence in the post-SFAS 130 period that OCI is priced on a dollar-for-dollar basis as is predicted by economic theory for transitory income items. We attribute this finding to our use of post-SFAS 130 as-reported measures of OCI rather than pre-SFAS 130 as-if estimates of OCI measures. Furthermore, we document that two components of OCI, foreign currency translation adjustment and unrealized gains/losses on available-for-sale securities, are priced by investors. In the post-SFAS 130 period, we also find that the type of financial statement in which firms report OCI and its components affects pricing, consistent with the conclusions of prior experimental research. However, our evidence suggests that investors pay greater attention to OCI information reported in the statement of changes in equity, rather than in a statement of financial performance. This could be attributed to investors becoming more familiar in the post-SFAS 130 period with the predominant reporting of OCI and its components in the statement of changes in equity.